2010
DOI: 10.1590/s1516-89132010000200029
|View full text |Cite
|
Sign up to set email alerts
|

Catechol biodegradation kinetics using Candida parapsilopsis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Pyrocatechol concentrations in each experiment were determined by DR4000 spectrophotometer by analyzing color with wavelength 600nm (26,27). Concentration of pyrocatechol wasmeasured after 2, 4, 6, 8, 10, 12, and 14 days ofexposure.…”
Section: Lab Studiesmentioning
confidence: 99%
“…Pyrocatechol concentrations in each experiment were determined by DR4000 spectrophotometer by analyzing color with wavelength 600nm (26,27). Concentration of pyrocatechol wasmeasured after 2, 4, 6, 8, 10, 12, and 14 days ofexposure.…”
Section: Lab Studiesmentioning
confidence: 99%
“… Pyne et al (2018) obtained a high-yield S. cerevisiae strain using CA 1,2-dioxygenase gene transfer and Aro1p engineering degradation technology. However, previous studies have revealed that CA can cause lethal toxicity in people and inhibit the growth and metabolism of microorganisms ( Kumar et al, 2005 ; Rigo et al, 2010 ; Maini Rekdal et al, 2020 ). Such harm manifests itself as NADH uncoupling and generation of large amounts of hydrogen peroxide when CA concentration rises as well as CA-induced irreversible damage to biological molecules such as DNA, proteins, and membranes in organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds such as catechol have been listed as priority-pollutants by EPA, USA [2,3]. Catechol is fatally toxic to fish at concentrations of 5–25 mg/L and it inhibits biological growth in microorganisms [4,5]. It has been detected in wastewater from coal conversion processes, crude wood tar, and drainage water from bituminous shale and in the outflow from coal-tar chemical production.…”
Section: Introductionmentioning
confidence: 99%
“…Many groups of aerobic bacteria are capable of using aromatic compounds as sole carbon and energy sources. There have been several reports on the biodegradation of catechol by some microbial strains under aerobic conditions such as Pseudomonas putida [4], Aspergillus awamori [14] and Candida parapsilopsis [5]. The bacterial strain Pseudomonas putida in a basal salt medium (BSM) at 29.9°C and pH 7 demonstrated the complete degradation of 500 mg/L of catecholin 94 h [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation